(untitled) (Journal of European Studies (JES), 2018)
This article evaluates the benefits and costs of the GSP+ scheme for Pakistan. It holds that although the scheme has commercially been fruitful for the economy, there might be long-term repercussions due to the lack of diversity in Pakistani products. In addition, the 27 conventions attached to the scheme still await implementation. There is a lack of coordination between state and the business sector. Besides, the relevant authorities are themselves oblivious of the terms of this commercial engagement between Islamabad and Brussels. The author concludes that unless rectified, the current state of affairs augur complications for Pakistan-EU economic relationship.